The Digital Teaching and Learning on Islamic Education Institutions and Their Sustainability in the New Normal Era - Dina Destari; Erna Adita Kusumawati (Aqlamuna: Journal of Educational Studies, 2023)
Islamic educational institutions had encountered globalization and modernizations for years. As the Covid-19 pandemic outbreak, the digital transformation became a must as a reaction and adaptation toward the situation and condition. This article investigates the digital teaching and learning on Islamic education institutions and their sustainability in the new normal era. The method applied in this article was qualitative content analysis method. The findings are: 1) Digital teaching and Learning is a new transformation organizing teaching and learning management using digital application. Covid-19 pandemic has taken its toll on all aspect of life, including education, particularly in teaching and learning activities. It went on virtually using various platforms; 2) the application of Information and Communication Technology (ICT) includes not only in the teaching and learning, but also in the evaluation; 3) the global pandemic demands Islamic education institutions to up-date the institutional system and to manage as well as control institutional activities; and 4) the future digital teaching and learning on Islamic education institutions cover sustainability of ICT, sustainability of human resource to adapt with the latest situation, and the sustainability of the institutions’ existence